DUKUNGAN SOSIAL PEER GROUP, KONTROL DIRI DAN KOMITMEN MAHASISWA PADA TUGAS PERKULIAHAN KEWIRAUSAHAAN - Ahmad Rizki Sridadi; Tri Siwi Agustina (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
Entrepreneurship course instructional’s objective is to provide in-depth insight and (first-hand experience on how to growing and developing the entrepreneurial spirit. In order to achieve these objectives in the learning process, the student must complete a thematical project is done in roups. The purpose of reseach is determining the level of students who programmed the course Entrepreneurship on duty obtained by involving social support pe-er group and self-control. Research conducted on students of management studies 3rd semester that follows Entrepreneurship Course. Number of subjects who had involved in filling out the questionnaire this study is 102 people. The study was conducted in the academic period even semester 2015 / 2014. The results showed that the peer group involving social support and self-control can simultaneously affect a student's commitment to the task of lecturing Entrepreneurship. But partially obtained different results where, peer group social support can affect a student's commitment to the task of lecturing Entrepreneurship., While the self-control has no effect on the student's commitment to the task of lecturing Entrepreneurship.